A time series analysis of oil production, rig count and crude oil price: Evidence from six U.S. oil producing regions. (15th February 2016) - Apergis, Nicholas; Ewing, Bradley T.; Payne, James E.
Abstract: With oil company valuations tied in part to oil well drilling to replace reserves at a rate that exceeds production, understanding the dynamic relationship between the development of oil rigs and oil production is important. This study focuses on the Bakken, Eagle Ford, Haynesville, Marcellus, Niobrara, and Permian regions, historically the six major oil producing regions in the U.S. Specifically, we apply time series econometric techniques of unit root, cointegration, and error correction modeling to examine the dynamic relationship among oil production, rig count, and crude oil prices for each of these six U.S. oil producing regions. The results of this study highlight the importance of identifying the regional variations in oil production, rig count, and crude oil prices and their interactions in both the valuation of oil firms and capital investment projects as it pertains to oil drilling activity. Highlights: This study focuses on the six major oil producing regions in the U.S. Examines the relationship among oil production, rig count, and oil prices. There are regional variations in oil production, rig count, and crude oil prices.